Psychological Effects of a 1-Month Meditation Retreat on Experienced Meditators: The Role of Non-attachment - Montero-Marin, Jesus; Puebla-Guedea, Marta; Herrera-Mercadal, Paola; Cebolla, Ausias; Soler, Joaquim; Demarzo, Marcelo; Vazquez, Carmelo; Rodríguez-Bornaetxea, Fernando; García-Campayo, Javier (Frontiers in Psychology, 2016)
Background. There are few studies devoted to assessing the impact of meditation-intensive retreats on the well-being, positive psychology and personality of experienced meditators. We aimed to assess whether a 1-month Vipassana retreat: a) would increase mindfulness and well-being; b) would increase prosocial personality traits; and c) whether psychological changes would be mediated and/or moderated by non-attachment. Method. A controlled, non-randomized, pre-post-intervention trial was used. The intervention group was a convenience sample (n=19) of experienced meditators who participated in a 1-month Vipassana meditation retreat. The control group (n=19) comprised matched experienced meditators who did not take part in the retreat. During the retreat, the mean duration of daily practice was 8-9 hours, the diet was vegetarian and silence was compulsory. The Experiences Questionnaire (EQ), Non-Attachment Scale (NAS), Positive and Negative Affect Schedule (PANAS), Satisfaction With Life Scale (SWLS), Temperament Character Inventory Revised (TCI-R-67), Five Facets Mindfulness Questionnaire (FFMQ), Self-Other Four Immeasurables (SOFI) and the MINDSENS Composite Index were administered. ANCOVAs and linear regression models were used to assess pre-post changes and mediation/moderation effects. Results. Compared to controls, retreatants showed increases in non-attachment, observing, MINDSENS, positive-affect, balance-affect and cooperativeness; and decreases in describing, negative-others, reward-dependence and self-directedness. Non-attachment had a mediating role in decentring, acting aware, non-reactivity, negative-affect, balance-affect and self-directedness; and a moderating role in describing and positive others, with both mediating and moderating effects on satisfaction with life. Conclusions. A 1-month Vipassana meditation retreat seems to yield improvements in mindfulness, well-being and personality, even in experienced meditators. Non-attachment might facilitate psychological improvements of meditation, making it possible to overcome possible ceiling effects ascribed to non-intensive practices.